Crescimento inicial, trocas gasosas e status hídrico de clones de eucalipto sob diferentes regimes de irrigação. - Tatagiba, Sandro Dan (2006)
The objective of this study was to evaluate the effect of the deficit water on the following growth characteristics: diameter of the stem; height of the plants; foliate area; relationship root/aerial part; dry matter: of the leaves, stem and branches, roo